The Impact of Rice Farm Insurance on The Income of Farmers In Indonesia - Silaban, Burju; Burhanuddin; Harmini (Jurnal Manajemen & Agribisnis, 2022)
The fluctuation of rice production in Indonesia over the last 5 years shows a downward trend due to a decrease in land area and increase risks. A government's effort to overcome the risks of rice farming is to establish rice farming insurance (AUTP). This research aims to analyze the factors that influence farmers' decisions to join rice farming insurance (AUTP) and how the impact of rice farming insurance on farming income in Indonesia. The data used was secondary data from the survey results from the Central Bureau of Statistics (BPS) in 2018. The number of samples was 470 farmers, consisting of 122 farmers who joined rice farming insurance and 358 farmers who did not take rice farming insurance. Data were analyzed using logistic regression and propensity score matching (PSM) methods. The results show that the variables of education level, participation in socialization, perceptions of decreased production, and production significantly influenced farmers' decisions to join rice farming insurance. The impact of insurance on farm income shows that the average farm income of farmers who follow rice farming insurance is higher than farmers who did not join rice farming insurance. Therefore, the government continued to encourage the implementation of the rice farming insurance program to increase the level of farmer participation and sustainability of the AUTP program. Keywords: income, participation rate, rice farming insurance, risk